Investing in early childhood: What can policymakers learn from Dynamics of Inequality Across the Life-course (DIAL) research? - Abrams Fran; Kilpi-Jakonen Elina (NORFACE, 2022)
There are a number of key European policy agendas related to early childhood on which the DIAL research can shed light. This policy brief gives an overview of findings from DIAL projects in this area.
Key Findings
Early childhood investments are key to social mobility, and inequalities which can be measured in early childhood have grown in recent years.
A range of pre-birth factors can be linked to later outcomes. Children born very pre-term or with very low birth weight are at greater risk of later issues such as lower IQ, mental ill-health or remaining unpartnered.
Toddlers who experience good mental and verbal stimulation and supportive parenting have more advanced language and social skills.
Both mothers’ education and fathers’ occupational status are linked to children’s educational outcomes.
Universal early childhood programmes can deliver significant health benefits.